Dinámica de los bosques alterados por vientos fuertes en la reserva nacional Alpahuayo Mishana, Iquitos, Perú. 2021 - Garcia Mozombite, Maria Mirian (2025)
This study was conducted in the Allpahuayo Mishana National Reserve, Iquitos, Peru. The objective was to determine the dynamics of the forests altered by strong winds, 100 sub plots of 30 x 15 meters were evaluated, the technique used corresponded to the continuous forest inventory with an inter-census period of 10.75 years. The annual mortality rate in the primary forest of the high zone was 3.5 % and in the low zone 2.7 %; while the secondary forests reported an annual rate of 5.8 % in the high zone and 4.1 % in the low zone. The annual recruitment rate in the primary forest in the high zone was 3.8 % and in the low zone 2.9 %; while secondary forests reported annual rates of 5.5 % and 4.2 % for the high zone and low zone, respectively. Secondary forests in low zones experience stress in terms of mortality and high dynamism, which could affect their long-term stability. The average lifespan for the different forest types was 27 years for primary forest in the high zone and 45 years in the low zone, 16 years for secondary forest in the high zone and 21 years in the low zone. The study highlights the vulnerability of secondary forests, especially in low areas, to disturbances and environmental changes, while primary forests show greater resilience and stability.